Sponsoring the football national team - Brochado, A.; Dionísio, P.; Leal, M. C. (Journal of Business and Industrial Marketing, 2018)
Purpose A key concern in sports sponsorship decisions is knowing under what conditions sponsorship can effectively act as a brand building tool. The purpose of this study is to list attributes to use when examining congruency in the sponsorship of national football teams. The second aim was to test whether being a client of the sponsor brand and being involved with the sponsee moderates the relationship between image congruence and sponsorship response. Design/methodology/approach Data were collected on four sponsors of the Portuguese national team, just before the 20th Fédération Internationale de Football Association World Cup. Analyses were conducted on a representative national sample of fans. The research design encompassed a two-step approach. First, qualitative analysis identified the main attributes that fans associate with the national team. In the second quantitative phase, moderated regression analysis was used to test the proposed model. Findings This study confirmed sponsor–sponsee congruence in seven attributes (i.e. national symbol, strength, strong emotions, happiness, optimism, connection and positive feelings) enhances positive brand image and fans’ involvement with the national team moderates this relationship. Positive sponsorship outcomes tend to be higher for sponsors when fans are currently clients of the sponsor brand. Originality/value This study adds to previous research by using mixed methods to study sponsor–sponsee congruence regarding national teams and by testing whether fans being clients of sponsors and being involved with sponsees moderate sponsor–sponsee congruence.